PENGGUNAAN BAHASA DALAM TEKS DESKRIPSI KARYA SISWA KELAS VII.6 SMP NEGERI 25 PADANG - Zulfikarni, Sri Hastuti, Harris Effendi Thahar, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This article is written to find out the application of language in student’s   description text at class VII.6 SMPN 25 Padang. Data in this study was language application in student’s description text at class VII.6 SMPN 25 Padang. Data source was student’s description text and sample was taken by purposive sampling technique to determine data source. Study instrument was writer and assisted with tables inventory data. Study finding shows that: first, student’s description text at class VII.6 SMPN 25 Padang mostly using general and location pronominal, and one student using feature pronominal. Second, most student using prefix and suffix in their description text, no student using infix, and two students do not use affix/confix. Third, mostly students using all types of phrases; only few of them do not completely use their phrase. Eleven students do not use nominative phrase in description text; twelve students do not use verb phrase in description text; five students do not use numeric phrase in description text; five students do not use adverb phrase in description text; and writer finds out that all students using preposition in their description text. Kata kunci: penggunaan bahasa, teks deskripsi, karya siswa kelas VII.6